Nonalcoholic fatty liver disease: Diagnostic biomarkers - Hadizadeh, Fatemeh (World J Gastrointest Pathophysiol, 2017)
Nonalcoholic fatty liver disease is a common medical condition worldwide and its prevalence has increased notably in the past few years due to the increases in prevalence of obesity and metabolic syndrome. However, diagnosis of this disease is still a matter of debate because of disease variations and pathophysiologic alterations. Specific single markers have gained considerable attention recently, among them markers related to hepatic pathophysiology, inflammation, adipocytokines and so forth. But, it seems that no single marker is sufficient for diagnosis and staging of the disease, and applying a panel including different types of tests may be more useful.